Improvement and standardization of a low-cost and nutritious skinless pork longanisa - Valdez, Maria Isabel C.
This is a study on the improvement and standardization of a low-cost and nutritious skinless pork longaniza. The researcher sought to: (1) determine the optimum level of TSP in BAI longaniza; (2) standardize the formulation and process; (3) compare the cost of production between the standardized formula and the pure pork longaniza. In Phase I, the optimum level of TSP was established through determination of the net yield, % WHC and % shrinkage of the longaniza prepared with different levels of TSP. The samples were also subjected to sensory evaluation. Results showed that the optimum level of TSP in BAI longaniza was at 50%. The product was found to have: (a) 42.5% WHC; (b) 20.9% shrinkage and, (c) net yield of 712.6 g/1 kg of the direct raw material. Analysis of the subjective tests showed that even with 50% TVP substitution, the product still rendered a highly acceptable product. Phase II standardized the formulation and process of the 50% TSP-substituted longaniza by objectively and subjectively comparing it with the all-meat longaniza. Results of the objective tests showed no significant difference between the two samples, in terms of: (a) % WHC; (b) % shrinkage; (c) pH; (d) % crude fat; (e) % crude protein; (f) texture and, (g) % moisture content. Results of the sensory evaluation on the other hand, showed that the 50% TSP-substituted longaniza has the same product as the control. In Phase III, the cost of production of the 50% TSP-substituted longaniza was found to be 10% cheaper than the all-meat longaniza (BAI price). Furthermore, consumer acceptability test indicated that the product has a high market potential.